The Effectiveness of Ginger, Lemon, and Honey Decoction in Reducing Nausea and Vomiting in Pregnant Women with Emesis Gravidarum: A Quasi-Experimental Study - Nurmasyithah, Nurmasyithah; Ariyanti, Ririn; Eka Permatasari, Annisa (Tropical Health and Medical Research, 2025)
Nausea and vomiting during pregnancy, or emesis gravidarum, can occur at any time and may persist into the second or third trimester, causing dehydration or severe complications if unmanaged. Ginger, lemon, and honey create a drink rich in vitamins, minerals, and enzymes beneficial for reducing these symptoms. This study aimed to analyze the effect of consuming a ginger, lemon, and honey decoction on pregnant women with emesis gravidarum at the Malinau City Health Center. Conducted from May to June 2024, this quasi-experimental study involved 30 participants divided into two groups: 15 in the Education group and 15 in the intervention group. The intervention involved consuming fresh ginger boiled with 3 cc of lemon juice and 1 tablespoon of honey twice daily for four days. Nausea and vomiting were measured using The Rhodes Index Nausea, Vomiting, and Retching (INVR), a validated questionnaire. Results showed a significant reduction in INVR scores in the intervention group compared to the Education group (p < 0.001). After four days, the mean score in the intervention group was 8.60, 2.53 points lower than the Education group (11.13). These findings demonstrate that consuming ginger, lemon, and honey decoction for four days effectively reduces nausea and vomiting in pregnant women.